Digital sensory marketing: integrating new technologies into multisensory online experience - Petit, O; Velasco, C; Spence, C (Elsevier, 2018)
People are increasingly purchasing (e.g., food, clothes) and consuming (e.g., movies, courses) online where, traditionally, the sensory interaction has mostly been limited to visual, and to a lesser extent auditory, inputs. However, other sensory interfaces (e.g., including touch screens, together with a range of virtual, and augmented solutions) are increasingly being made available to people to interact online. Moreover, recent progress in the field of human-computer interaction means that online environments will likely engage more of the senses and become more connected with offline environments in the coming years. This expansion will likely coincide with an increasing engagement with the consumer’s more emotional senses, namely touch/haptics, and possibly even olfaction. Forward-thinking marketers and researchers will therefore need to appropriate the latest tools/technologies in order to deliver richer online experiences for tomorrow’s consumers. This review is designed to help the interested reader better understand what sensory marketing in a digital context can offer, thus hopefully opening the way for further research and development in the area.